2016
DOI: 10.4137/cpath.s38476
|View full text |Cite
|
Sign up to set email alerts
|

Phyllodes Tumor in a Lactating Breast

Abstract: Phyllodes tumor is attributed to a small fraction of primary tumors of the breast. Such tumors occur rarely in pregnancy and lactation. We report a case of a 25-year-old lactating mother presenting with a lump in the left breast. Core needle biopsy was opined as phyllodes tumor with lactational changes, and subsequent wide local excision confirmed the diagnosis of benign phyllodes tumor with lactational changes. The characteristic gross and microscopic findings of a well-circumscribed lesion with leaf-like fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 18 publications
0
16
0
1
Order By: Relevance
“…Previous review articles on this subject consisted of 7 patients (one bilateral: 8 tumors), 10 9 patients (one bilateral: 10 tumors), 29 and 14 patients (one bilateral: 16 tumors). 35 The mean age of patients in this study was 31 years (21-43 years), younger than the average of 40-45 years for usual PT 50 ; this difference is ordinary because gestational tumors are studied. The youngest patient was 21 and the oldest 43 years old.…”
Section: Discussionmentioning
confidence: 71%
“…Previous review articles on this subject consisted of 7 patients (one bilateral: 8 tumors), 10 9 patients (one bilateral: 10 tumors), 29 and 14 patients (one bilateral: 16 tumors). 35 The mean age of patients in this study was 31 years (21-43 years), younger than the average of 40-45 years for usual PT 50 ; this difference is ordinary because gestational tumors are studied. The youngest patient was 21 and the oldest 43 years old.…”
Section: Discussionmentioning
confidence: 71%
“…Murthy et al [15] reported a 25-year-old lactating mother presenting with a lump in the left breast that gross photograph of her specimen demonstrating a grayishwhite well-circumscribed mass with solid and cystic areas. Microscopic findings include fibroepithelial proliferation in a classic leaf-like pattern.…”
Section: Discussionmentioning
confidence: 99%
“…Fibroadenoma (FA) of the breast is a heterogeneous group of bidirectionally-differentiated tumors with proliferation of both epithelial and stromal components in young women, which belongs to fibroepithelial tumors together with PT. It has been reported in the literature that there are similar gene mutations in PT and FA [ 5 ], so some scholars believe that FA can be converted into PT. However, FA does not actually contain real tumor cells as PT does; therefore, they are two diseases of different types.…”
Section: Introductionmentioning
confidence: 99%